To a question of a choice of the generalized model of the traffic computer network - Гузий, Н. Н.; Минаев, Ю. Н.; Филимонова, О. Ю. (Problems of Informatization and Control, 2007)
Considers questions of construction of the generalized model of the network traffic on the basis of representation of set of parameters of the standard traffic in the form of a vector which components are functions invariants of tenzor the second rank. The opportunity of identification of attack to a computer network is shown